Acordos administrativos substitutivos de sanção - Silva, Victor Carvalho Pessoa de Barros e (2019)
This essay intends to probe the subject of consensuality, related to the substitutive agreements for administrative sanction. From a theoretical and normative observation, it is possible to infer that consensuality is increasingly available to provide the use of means more efficient by the Public Administration to succeeded in its functions. In the sanctioning scenario it is no different. The choice of consensus over administrative sanctions is increasingly standardized and widespread in order to increase the security of agreed parties and create a consensual culture. However, although a negotiation can be seen as a mechanism for administrative management, it has some barriers, as its implementation entails a derogation from certain state prerogatives. Thus, it is proposed to detail the instruments that materialize the substitutive agreements for administrative sanction and to track their common regulatory aspects, as a way of standardizing and verifying greater predictability for consensual administrative action. The first chapter portrays the evolution of administrative law with the corresponding consensus adjustment. In the second, there is a confrontation of pros and cons arguments for the adoption of substitutive agreements for administrative sanction. Subsequently, the study is dedicated to the definition, positivization, legal nature and instrumentalization of substitute agreements for administrative sanction. Finally, the controversies, the problems and challenges identified in the practice of substitutive agreements for administrative sanction are presented from the singularization of the regulatory aspects. In conclusion, the questions and proposals outlined throughout the dissertation are summarized